2001
DOI: 10.1029/2000gl012239
|View full text |Cite
|
Sign up to set email alerts
|

Propagation analysis of plasmaspheric hiss using Polar PWI measurements

Abstract: Abstract. We have analyzed high-rate waveform data, taken Storey et al. [1991] however observed hiss emissions even by the POLAR Plasma Wave Instrument at high altitudes in when, after long periods of magnetic calm, the plasmapause the equatorial plasmasphere, to study plasmaspheric hiss in the was absent. They also found that the waves often propagate at range of frequencies between 100 Hz and several kHz. These large angles from B0, even in the equatorial region. This means emissions are found almost everyw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 15 publications
3
84
1
1
Order By: Relevance
“…This is illustrated in panels (b)-(d), where the ray undergoes a well-defined sequence of reflections and equatorial crossings in the order: (MR-EQ-MR)-(PR-EQ-PR)-(MR-EQ-MR)-, etc. Panel (d) shows that whenever the ray crosses the equator, its wave normal angle is roughly field-aligned (an integer multiple of 1801), in agreement with recent observations that have indicated that plasmaspheric hiss occurs with roughly field-aligned wave normal angles (Santolik et al, 2001).…”
Section: Article In Presssupporting
confidence: 81%
“…This is illustrated in panels (b)-(d), where the ray undergoes a well-defined sequence of reflections and equatorial crossings in the order: (MR-EQ-MR)-(PR-EQ-PR)-(MR-EQ-MR)-, etc. Panel (d) shows that whenever the ray crosses the equator, its wave normal angle is roughly field-aligned (an integer multiple of 1801), in agreement with recent observations that have indicated that plasmaspheric hiss occurs with roughly field-aligned wave normal angles (Santolik et al, 2001).…”
Section: Article In Presssupporting
confidence: 81%
“…The first row shows the computed pitch-angle diffusion coefficients using the assumption of parallel propagation for the specified energies. The assumption of parallel propagation is justified by the case study of Santolik et al (2001). In addition, comparison of simulations with various assumptions of wave-normal angle distributions show that the observed scattering rates are best reproduced in simulations using small wave-normal angles, indicating that the waves are predominantly field-aligned .…”
Section: Local Loss Processes Inside the Plasmaspherementioning
confidence: 84%
“…We use continuous measurements of the Spatio-Temporal Analysis of Field Fluctuations-Spectrum Analyzer (STAFF-SA) instrument (Cornilleau-Wehrlin et al 1997). The presence of whistler-mode emissions is identified from the measured power-spectral densities and from analysis of the wave polarization (Santolik et al 2001. High-resolution waveform observations of the Wideband Data (WBD) instrument ) have been used to verify presence of the discrete frequency-time structures of chorus wave packets (Santolik et al 2014b).…”
Section: Methodsmentioning
confidence: 99%